2019
DOI: 10.1002/ijc.32086
|View full text |Cite
|
Sign up to set email alerts
|

Dental fluorosis and oral health in the African Esophageal Cancer Corridor: Findings from the Kenya ESCCAPE case–control study and a pan‐African perspective

Abstract: There are no studies of oral health in relation to esophageal cancer in Africa, or of Eastern Africa's endemic dental fluorosis, an irreversible enamel hypo‐mineralization due to early‐life excessive fluoride intake. During 2014–18, we conducted a case–control study of squamous cell esophageal cancer in Eldoret, western Kenya. Odds ratios (AORs (95% confidence intervals)) were adjusted for design factors, tobacco, alcohol, ethnicity, education, oral hygiene and missing/decayed teeth. Esophageal cancer cases (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 30 publications
4
78
2
2
Order By: Relevance
“…Of the 37 studies on risk factors for EC, 18 (48.6%) were conducted in South Africa[10,70-86], 5 (13.5%) in Kenya[11,13,87-89], 3 (8.1%) in Uganda[4,5,90], 2 each in Ghana (5.4%)[7,91], Zambia (5.4%)[3,92] and Zimbabwe (5.4%)[93,94], and 1 each in Malawi (2.7%)[95], Ethiopia (2.7%)[12], Tanzania (2.7%)[6], Egypt (2.7%)[96] and Nigeria (2.7%)[97].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 37 studies on risk factors for EC, 18 (48.6%) were conducted in South Africa[10,70-86], 5 (13.5%) in Kenya[11,13,87-89], 3 (8.1%) in Uganda[4,5,90], 2 each in Ghana (5.4%)[7,91], Zambia (5.4%)[3,92] and Zimbabwe (5.4%)[93,94], and 1 each in Malawi (2.7%)[95], Ethiopia (2.7%)[12], Tanzania (2.7%)[6], Egypt (2.7%)[96] and Nigeria (2.7%)[97].…”
Section: Resultsmentioning
confidence: 99%
“…Tooth loss, cooking, hot beverage consumption, dental fluorosis and using mursik: Tooth loss, cooking, hot beverage consumption and using mursik were found to be associated with EC in the Rift Valley of Kenya, OR 5.28, 95%CI: 2.98-9.41; OR 2.32, 95%CI: 1.41-3.84; OR 12.78, 95%CI: 6.98-23.6; and OR 3.72, 95%CI: 1.96-7.14 respectively[88]. Menya et al[11] conducted a case control study in Kenya evaluating the association of dental fluorosis and EC. They assessed association of EC with tobacco use, alcohol consumption, education, oral hygiene and missing/decayed teeth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also discovered to be associated with a particular tumor stages. Most recently, Menya 6 suggested that moderate/severe dental fluorosis was strongly associated with a 9.4-fold increased risk of esophageal squamous cell carcinoma (ESCC) compared with a no dental fluorosis population in Africa. In this study, F. nucleatum was significantly enriched in the M&S group and significantly higher than the Mild and Healthy groups.…”
Section: Discussionmentioning
confidence: 99%